MICROBIAL ACTIVITY of DARK RED LATOSOL SAMPLES STORED AT DIFFERENT TEMPERATURES - Vieira, Francisco Cleber Sousa; Nahas, Ely [UNESP] (Sociedade Brasileira de Microbiologia, 1998)
Foi determinada a atividade enzimática de amostras de solo armazenadas às temperaturas de 5, -12oC e ambiente durante 0-32 semanas. A atividade da fosfatase alcalina e da desidrogenase diminuiu nas amostras armazenadas a baixas temperaturas, enquanto que a atividade da fosfatase ácida não variou em relação ao controle.

The enzymatic activity of soil samples stored at temperatures of 5 to -12oC and at room temperature for 0-32 weeks was determined. While alkaline phosphatase and dehydrogenase activity was decreased compared to control in samples stored at low temperatures, acid phosphatase activity showed no significant change.
Keywords: Fosfatase; desidrogenase; armazenagem de solo; Phosphatase; dehydrogenase; soil storage